Resultado perinatal de fetos com malformações do trato urinário - Macedo, Maria Letícia Sperandéo de [UNESP]; Consonni, Marcos [UNESP]; Borges, Vera Therezinha Medeiros [UNESP]; Calderon, Iracema de Mattos Paranhos [UNESP]; Rudge, Marilza Vieira Cunha [UNESP] (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2003)
PURPOSE: to evaluate the perinatal outcome of fetuses with congenital anomalies of the urinary tract. METHODS: we reviewed the perinatal outcome of 35 fetuses with congenital anomalies of the urinary tract. The following characteristics related to the uropathy were analyzed: type (hydronephrosis, dysplasia and renal agenesis), side of lesion (bilateral or unilateral), and level of the obstruction (high or low, in hydronephrosis). The perinatal outcome was evaluated according to these characteristics. The data were analyzed by the c² test and by the exact Fisher test. The level of significance was 0.05. RESULTS: the incidence of hydronephrosis was 68.6%. Half of the fetuses had unilateral hydronephrosis. Renal dysplasia occurred in 17.1% of the cases; 83.3% of these were bilateral and 16.7%, unilateral. The incidence of renal agenesis was 14.3%, all bilateral. The fetuses with dysplasia/agenesis had a 91% incidence of oligohydramnios, preterm birth, low birth weight, and death. In the group with bilateral disease the presence of oligohydramnios, preterm birth, low birth weight, death, urinary tract infections, and the need of hospitalization for a period greater than 7 days was significant when compared to the group with unilateral disease. The need of hospitalization for a period greater than 7 days in patients with low obstruction was significantly higher when compared to the patients with high obstruction. CONCLUSIONS: hydronephrosis, bilateral disease, and lower obstruction were the most frequent uropathies. The dysplasia/agenesis group had a worse prognosis when compared with the hydronephrosis group. Bilateral disease had a worse prognosis when compared with the unilateral disease group. In the low obstruction group, the need for a period of hospitalization greater than seven days was higher than in the high obstruction group.

OBJETIVO: analisar a evolução perinatal de fetos portadores de malformações do trato urinário. MÉTODOS: estudo retrospectivo envolvendo 35 fetos portadores de malformações do trato urinário. As malformações foram classificadas de acordo com as seguintes características: tipo de uropatia e acometimento. As uropatias estudadas foram: hidronefrose, classificada em alta e baixa, displasia e agenesia renal; quanto à lateralidade da malformação, foi considerado o acometimento uni e bilateral. O resultado perinatal foi confrontado com as características citadas. A análise estatística foi realizada usando-se o teste do c² e teste exato de Fisher, sendo adotado 5% como limite de significância (p<0,05). RESULTADOS: a incidência de hidronefrose foi de 68,6% e o acometimento foi bilateral em metade destes fetos. Displasia renal ocorreu em 17,1% e, em 83,3% destes, foi bilateral. A incidência de agenesia renal foi de 14,3%, sendo sempre bilateral. No grupo displasia/agenesia observou-se 91% de oligoâmnio, prematuridade, baixo peso ao nascimento e de óbito. Nos casos de uropatia bilateral foi significativa a ocorrência de oligoâmnio, prematuridade, baixo peso, óbito, infecção do trato urinário e permanência hospitalar por mais de sete dias. Entre os fetos com obstrução baixa, a permanência hospitalar por mais de sete dias foi significativa. CONCLUSÕES: neste estudo, foram mais freqüentes o acometimento bilateral e a hidronefrose e, dentre elas, as obstruções baixas; o grupo displasia/agenesia apresentou pior prognóstico quando comparado ao grupo hidronefrose; o acometimento renal bilateral determinou pior prognóstico em relação àqueles com acometimento unilateral; a obstrução baixa do trato urinário determinou maior tempo de internação em relação às obstruções altas.
Perinatal outcome of fetuses with congenital uropathies
Keywords: Malformações fetais e prematuridade; Ultra-sonografia; Resultado perinatal; Fetal malformations; Uropathies; Ultrasound; Perinatal outcome